Body mass index and risk of age-related cataract: a meta-analysis of prospective cohort studies. - Juan Ye; Li-Xia Lou; Jin-Jing He; Yu-Feng Xu (PLoS ONE)
Background Age-related cataract (ARC) is the leading cause of blindness in the world. The relationship between body mass index (BMI) and risk of ARC is controversial across observational studies. We therefore performed this meta-analysis to evaluate the association between BMI and risk of ARC. Methods Eligible studies were identified through an electronic search of PubMed, Embase and the Cochrane Library. We pooled study-specific relative risks (RRs) and 95% confidence intervals (CIs) to determine the risk of ARC associated with BMI categories and per 1 kg/m² increase in BMI. Results A total of 17 prospective cohort studies were included in the meta-analysis. The pooled RRs of ARC were 1.08 (95% CI, 1.01-1.16) for overweight and 1.19 (95% CI, 1.10-1.28) for obesity compared with normal weight. These findings were robust when stratified by sex, sample source, outcome types and confounders, while significantly differed by assessment of BMI and ARC, and duration of follow-up. The summary RR suggested that per 1 kg/m² increase in BMI was associated with a 2% increased risk of ARC (RR 1.02, 95% CI 1.01-1.03). Pooled estimates of RRs consistently indicated a trend for subjects with a high BMI to develop posterior subcapsular cataracts (RR 1.19, 95% CI 1.06-1.35, for overweight; RR 1.50, 95% CI 1.24-1.81, for obesity; RR 1.04, 95% CI 1.01-1.06, per 1 kg/m² increase in BMI) other than nuclear or cortical cataracts. Conclusions The overall findings suggest that elevated BMI may increase the risk of ARC, especially posterior subcapsular cataracts. Further trials are needed to investigate the effect of weight reduction in obese populations on the risk of ARC.